KEADILAN SUAMI YANG BERPOLIGAMI DALAM PERSPEKTIF KLASIK, KONTEMPORER, DAN KEINDONESIAAN - abdulahanaa, abdulahanaa (PSW, 2012)
Via this study, reader is introduced about polygamy in classic view, contemporer view and Indonesian perspective. So implication is pictured clearly that apparently marriage problem of classic term thus far have experienced developing that regarded by culture and trend is epoch. Mohammed Aawâs words about polygamy needs interpretation and correlation with cultural context of marries that already happens various cleft the world in particular at Arabic peninsula on term before islam coming,Â later and thus far. Reader is expected to get understanding about polygamyâs essence and justice meaning in their family. One presumably it gets to be reached, therefore focuses west critics and Islamic liberal streaming can be answered scientifically and factual as it were has already been described on study.